2010
DOI: 10.1177/1359105309345168
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal and Self-regulation Determinants of Healthy and Unhealthy Eating Behavior in Adolescents

Abstract: The purpose of this study was to investigate the influence of interpersonal and personal factors on (un)healthy eating in adolescents. The study sample consisted of 473 adolescents. Regression analyses were conducted to examine the effect of family climate, peer influence and self-regulation cognitions (goal commitment, efficacy and ownership) on healthy and unhealthy eating. Self-regulation cognitions are positively related to healthy eating and negatively to unhealthy eating. We conclude that different aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 39 publications
5
48
1
3
Order By: Relevance
“…As in previous studies [20, 38, 42], both family and peer support were associated with F&V intake, although only significantly so in the non-minority sample. It is not clear why social support did not predict intake in the minority sample; however, low statistical power may have been an issue in these analyses as indicated by the power analysis results.…”
Section: Discussionsupporting
confidence: 81%
“…As in previous studies [20, 38, 42], both family and peer support were associated with F&V intake, although only significantly so in the non-minority sample. It is not clear why social support did not predict intake in the minority sample; however, low statistical power may have been an issue in these analyses as indicated by the power analysis results.…”
Section: Discussionsupporting
confidence: 81%
“…Although previous research has documented a variety of strategies that adults may employ in self-regulating their eating behavior, attempts to document the strategies that adolescents use to ensure their healthy eating are scarce. Only one study aimed to investigate adolescents eating self-regulation [9], but this study describes so-called self-regulation cognitions rather than actual strategies that can be employed to improve self-regulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary evidence supports this theoretical framework for addressing adolescent obesity, 45,46 and highlighting the importance of improvement in self-efficacy and self-regulation as key for the promotion of health 47-51 and adolescent well-being in various psychosocial domains. 14,52,53 Moreover, the role of self-efficacy in mediating connections between health behavior and mental health, such as depression, has been shown in recent studies addressing multiple health outcomes.…”
mentioning
confidence: 73%
“…The CLIMB's ability to improve family support for youth's health behavior change is critically important, given that social context, and especially the role of the family context, has been implicated as critical in interventions that target prevention and control of obesity-related behaviors. 45,46 Recent evidence, for example, indicated that family-based weight loss interventions are effective at health outcomes including daily fruit intake, physical activity, and sedentary behavior 45,46 and, more specifically, that parent-adolescent communication influences sedentary behavior. 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation